2014
DOI: 10.1186/scrt394
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord tissue-derived mesenchymal stromal cells attenuate remodeling after myocardial infarction by proangiogenic, antiapoptotic, and endogenous cell-activation mechanisms

Abstract: IntroductionAmong the plethora of cells under investigation to restore a functional myocardium, mesenchymal stromal cells (MSCs) have been granted considerable interest. However, whereas the beneficial effects of bone marrow MSCs (BM-MSCs) in the context of the diseased heart are widely reported, data are still scarce on MSCs from the umbilical cord matrix (UCM-MSCs). Herein we report on the effect of UCM-MSC transplantation to the infarcted murine heart, seconded by the dissection of the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 61 publications
6
97
1
1
Order By: Relevance
“…Kim et al had shown that the transplantation of UCMSCs in patients with Buerger's disease showed improvement in the symptoms along with increase in the number and size of capillaries [36]. Other similar studies have implicated paracrine factors secreted by UCMSCs to be responsible for improved angiogenesis [37,38]. In these reported studies, the paracrine factors responsible for the angiogenic response have not been elucidated.…”
Section: Introductionmentioning
confidence: 40%
“…Kim et al had shown that the transplantation of UCMSCs in patients with Buerger's disease showed improvement in the symptoms along with increase in the number and size of capillaries [36]. Other similar studies have implicated paracrine factors secreted by UCMSCs to be responsible for improved angiogenesis [37,38]. In these reported studies, the paracrine factors responsible for the angiogenic response have not been elucidated.…”
Section: Introductionmentioning
confidence: 40%
“…Numerous studies have demonstrated that MSC therapy has great promise for regenerating damaged myocardium [15,16]. However, the efficacy of the therapy is limited by the poor viability of MSCs transplanted into the infracted heart [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It is also conceivable that growth factors and cytokines produced by transplanted cells in general might play a role in the proliferation, mobilization, differentiation, and/or survival of endogenous CPCs. We have recently demonstrated that noncardiac Wharton's jelly mesenchymal stem/stromal cells are able to stimulate Sca-1 + CPCs proliferation and to activate a cardiomyogenic program through secreted factors [63]. Comprehensive investigations are also lacking on the ability of Sca-1 + CPCs to modulate their nesting microenvironment.…”
Section: Fig 1 Heart Resident Sca-1mentioning
confidence: 99%